2005
DOI: 10.1093/ndt/gfi206
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric X-ray absorptiometry in the assessment of vertebral fractures in renal transplant patients

Abstract: Prevalence of vertebral fractures in renal transplant patients is quite high and randomly associated with reduced BMD. A surveillance of the spine by Rx, implemented with vertebral morphometry, is therefore warranted to recognize the disease. (MXA is a reliable alternative technique, especially in more severely affected individuals.) MXA, although less sensitive than the conventional techniques because of possible technical biases, is very specific, and can be proposed for follow-up purposes in this population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
3
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
4
22
3
2
Order By: Relevance
“…These findings confirmed our previous results in a small group of recipients . Lower prevalence has been reported in patients with shorter follow‐up . However, our results agreed with those reported by Giannini et al.…”
Section: Discussionsupporting
confidence: 94%
“…These findings confirmed our previous results in a small group of recipients . Lower prevalence has been reported in patients with shorter follow‐up . However, our results agreed with those reported by Giannini et al.…”
Section: Discussionsupporting
confidence: 94%
“…In accordance with the previous studies [10,11,12,13], approximately 65% of our RT recipients had osteopenia/osteoporosis, which was more than two times higher than the rate observed in control subjects. Significant reductions in femur total BMD, femur total T- and femur total Z-scores indicated that the femur was effected more markedly than the other bones since whole-body BMD, whole-body T- and whole-body Z-scores were similar to those in control subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Bone losses in short terms develop quickly [4,5,6,7] in ranges of 7-10% in the first year following renal transplantation [8,9]. Nevertheless, the prevalence of osteopenia or osteoporosis reaches 70% in long-term follow-ups [10,11,12,13,] which increases the risk of bone fractures [11,14]. Although the immune suppressive drugs are considered the main reason for bone loss after renal transplantation, the duration of renal failure and time on dialysis, resistant metabolic acidosis, secondary hyperparathyroidism, post-transplantation hypophosphatemia, hypogonadism, advanced age, female gender, accumulation of aluminum or β2-microglobuline, diabetes mellitus, smoking and vitamin D deficiency may also contribute in the process [3,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Also the "normal" subjects can then be excluded prior to performing conventional radiographs and further time-consuming and costly methods of vertebral deformity assessment such as SQ by an experienced radiologist and/or quantitative morphometry. Also, with its low radiation and good precision, IVA could be utilized to identify vertebral fractures in populations affected by conditions different from osteoporosis, but with high vertebral fracture risk, i.e., liver or kidney transplant patients [93,94].…”
Section: Assessment Of Vertebral Fractures On Dxa Imagesmentioning
confidence: 99%